Confidence Intervals for Welfare Measures with Application to a Problem of Truncated Counts - Creel, Michael D.; Loomis, John B. (The Review of Economics and Statistics, 1991)
Michael D. Creel, John B. Loomis, Confidence Intervals for Welfare Measures with Application to a Problem of Truncated Counts, The Review of Economics and Statistics, Vol. 73, No. 2 (May, 1991), pp. 370-373